2012
DOI: 10.1002/eco.1322
|View full text |Cite
|
Sign up to set email alerts
|

Growing season variability in evapotranspiration, ecosystem water use efficiency, and energy partitioning in switchgrass

Abstract: Evapotranspiration (ET), ecosystem water use efficiency (EWUE), and energy partitioning in switchgrass (Panicum virgatum L.) ecosystems are crucial to understand its water and energy balances since switchgrass acreage is expanding for cellulosic biofuels. We measured CO2, H2O, and energy fluxes over a switchgrass field in Chickasha, OK, USA, using eddy covariance method. The objective of this study was to quantify seasonal variations in ET, EWUE, and seasonal distributions of energy partitioning in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…3 Seasonal changes (8-day averages) of ecosystem water use efficiency (EWUE GPP and EWUE NEP ) based on gross primary production (GPP) and evapotranspiration (ET) and net ecosystem production (NEP) and ET at ten forest sites, respectively ecosystem level: GPP or ER (which includes both autotrophic and heterotrophic respiration) in response to environmental effects ). In addition, carbon uptake (NEE or GPP) is constrained more than ET by VPD through restriction of stomatal regulation (Kuglitsch et al 2008;Wagle and Kakani 2014). The wavelet analysis showed that NEE and ET deviated from each other at seasonal-to-interannual timescales at all ENFs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…3 Seasonal changes (8-day averages) of ecosystem water use efficiency (EWUE GPP and EWUE NEP ) based on gross primary production (GPP) and evapotranspiration (ET) and net ecosystem production (NEP) and ET at ten forest sites, respectively ecosystem level: GPP or ER (which includes both autotrophic and heterotrophic respiration) in response to environmental effects ). In addition, carbon uptake (NEE or GPP) is constrained more than ET by VPD through restriction of stomatal regulation (Kuglitsch et al 2008;Wagle and Kakani 2014). The wavelet analysis showed that NEE and ET deviated from each other at seasonal-to-interannual timescales at all ENFs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The slopes of these linear relationships forced to zero are a good representation of the WUE (Wagle and Kakani, 2012) and are very close to the WUE values found as ratio between NEE and ET, cumulated at seasonal scale in the same period. In this case the slopes are not significantly different (ANCOVA P=0.71) even if the correlations are very strong.…”
mentioning
confidence: 65%
“…Except for the senescence phase, in accordance with Emmerich (2007) and Wagle and Kakani (2012), daily WUE values along the seasons, show a great variability, ranging between -0.89 and -41.68 gCO2 kgH2O -1 in the WS and between 0.12 and -42.68 gCO2 kgH2O -1 in the DS. This variability is due to the effects of weather and plant physiology on CO2 and ET fluxes.…”
Section: Daily Scalementioning
confidence: 99%
See 1 more Smart Citation
“…tolerance during establishment [64], possibly because of lower water use efficiency related to lower carbon assimilation during drought [111]. Although when drought was imposed after establishment, Panicum virgatum plants appeared to be drought hardy [64,65]-particularly upland cytotypes [67,68].…”
Section: C4mentioning
confidence: 99%